Birth control battles how race and class divided American religion - Wilde, Melissa J., 1974- (University of California Press, 2020)
"Conservative and progressive religious groups fiercely disagree about issues of sex and gender. But how did we get here? Sociologist Melissa J. Wilde shows us how today's modern divisions began in the 1930s in the earliest public battles over birth control and not for the reasons we might expect today. By examining thirty of America's most prominent religious groups-including Mormons, Methodists, Southern Baptists, Seventh Day Adventists, Quakers, Jews, and more-Wilde contends that fights over birth control were never about sex, women's rights, or privacy but were actually about race, class, and white supremacist concerns about undesirable fertility. Using census and archival data and more than 10,000 articles, statements, and sermons from religious and secular periodicals, Wilde chronicles the religious community's division on contraception. She takes us from the 1930s, when support for the eugenics movement saw birth control as an act of duty for less desirable groups, to the 1960s, when religious identities had crystalized to such an extent that most congregants had forgotten the roots of their stance on birth control. Charting the twists and turns of how reproductive politics were tied to complex views of race, immigration, and manifest destiny, Birth Control Battles shows the enduring importance of race and class for American religion as it rewrites our understandings of what it has meant to be progressive or conservative in America"--Provided by publisher